THE USE OF PHRASEOLOGICAL UNITS IN THE ENGLISH LANGUAGE EDUCATIONAL DISCOURSE - BKHINDER, Natalia (Науковий вісник Ужгородського університету. Серія Філологія, 2020)
The article deals with definition of English language discourse as a combination of mental and speech actions performed by subjects of educational process at the English language classroom. The author proves that educational discourse concerns knowledge and skills transferring, establishment relations between educational process subjects and evaluation of language competence of those who learn. Phraseological units are considered to be a significant property of English language educational discourse as they help the discourse be more effective and get students more motivated. Also, we assume that the proper usage of phraseological units in the English language classroom makes the educational process better and more focused on foreign language learning. The author analyzed three different approaches to classification of phraseological units in English language educational discourse and provided the examples to illustrate the types definitions. We have come to the conclusion that native and foreign classification vary as they are based on different criteria and linguistic characteristics. Besides, we offer that the knowledge of idioms is an indicator of high level English language competence of students and precondition of their professional competence as they will be able to perform professional duties by means of foreign language and consider social and cultural peculiarities of foreign language speakers. To realize this, we investigated the requirements to incorporation of phraseological units within the learning process and found out that some types of exercises can be effective; context analysis of new vocabulary and collaborative learning. The author proves that phraseological units should be widely used in the English language classroom while explaining new material, commenting on students’ behaviour and achievements, developing instructional materials or courseware.